Novel approach for better compliance of mask during COVID pandemic - Anshul Chaudhry; Girish Chaudhary; Abhimanyu Kochhar (Elsevier, 2021)
COVID 19, started as a respiratory illness has affected the human life world-wide. Mandatory guidelines for wearing of masks have been issued by WHO even if you are stepping out. The continuous wearing of masks for prolonged duration has led to some negative consequences. Material and method: A new method was introduced to increase the compliance of mask by using easily available orthodontic wires in the dental set up. Results: The new approach was helpful in getting rid of rashes, irritation and erythematous patches behind the ears along with the reduction in the chances of cross contamination. Conclusion: This method can be incorporated in routine in the dental practice, even when one is not working on the patient.